Population and reproductive health in India: an assessment at the current situation and future needs - Jejeebhoy, Shireen J....[et.al] (New Delhi, 2014)
Synthesizing both qualitative and quantitative data on youth, gender, reproductive health and rights and population, from a variety of sources, this volume presents a composite assessment of the situation and provides directions for government strategies and programmes.
Keywords: Population